Quality assurance and effectiveness of management learning electricity magnet with acculturation nontoni (observation), niteni (whereas), niroke (imitating), and nambahi (add) - Sunarto Sunarto (Universitas Sarjanawiyata Tamansiswa, 2017)
The objective study to knowing the quality assurance and effectiveness of student learning outcomes in the cognitive competence, psychomotor, and effective with acculturation models nontoni (observation), neteni (remembering), neroke (imitating), (4) nambahi (add) on activities, namely:Â (1)Â Â learning cooperative, (2) conducting experiments, and (3) report experiments. Subjects were learning quality assurance management magnetic electricity in the third semester student number 39 students. The location of research is in the Physical Education Studies Program Faculty of Teacher Training and Education Sciences University of Sarjanawiyata Tamansiswa. This data collection techniques use the instrument objective multiple choice test, observation sheet Likert scale models, and documentation. Qualitative data analysis technique is to determine the effectiveness of the quality assurance and learning outcomes of students in courses magnetic electricity. Results of research on learning with acculturation models notoni, neteni, neroke and nambahi using cooperative learning approach, experiment, and documentation of student reports obtained an average score of 83.45 entry predicate good or trustworthy. In order for the result to be very trustworthy increase expected no improvement in the management of cooperative learning, experiment equipment, coaching in preparing the trial reports, and worksheets student learning.